PERSEPSI DAN MINAT SISWA KELAS VII EKSTRAKURIKULER SEPAK BOLA DI SMP N 1 PENGKADAN KAPUAS HULU - Tri Akbar; Ahmad Atiq; Muhammad Mimi Haetami (Universitas Tanjungpura, 2021)
AbstractPangkadan Kapuashulu Junior High School 1 has many students in VII class who arevery interested in football extracurricular but never know whether the taste is still thereis not so the best way is to conduct research which is based on perceptions andextracurricular interest in football. The research method used in this study is aquantitative method with the form of survey research. The population in this study uses atotal sample of 80 students in class VII. The results of the research are that students atSMP N 1 Pangkadan Kapuashulu have student perceptions. Football extracurricular byanswering yes 1,125 with a percentage of yes 90% and 155 with a category of no with a10% percentage. Research with data on male student interests is 2117 yes with apercentage of 90% and 203 answering no with 10%. That every male student has a greatopportunity In order to convey his talents and interests to realize what will be developed,including the perception and interest of the extracurricular football.Keywords: Football, Extracurricular, Interests, Perceptions